Evaluation of the use of different prophylactic antibiotic protocols in surgically assisted rapid maxillary expansion: A controlled, double-blind, randomized clinical study (Research, Society and Development, 2021)
Data related to postoperative infection in surgically-assisted rapid maxillary expansion (SARME) are scarce. Our goal was to compare the effects of two different prophylactic antibiotic regimens on infection rates in patients undergoing SARME. A randomized, double-blind clinical trial was carried out with 23 patients (06 men and 17 women) who received 1g cefazolin one hour before the procedure (Group 1 – G1) or 1g cefazolin one hour before the procedure and again in the first 24 postoperative hours (Group 2 – G2). Patients were followed up for one month after surgery. Pain was greater in G1 with a statistically significant difference in the follow-ups of 1, 2, 7 and 21 postoperative days (p